1890 Ala. Laws 1317 - (:unkn) unknown (My University, 1890)
Approved the town of Decatur to require licensing but also placed a maximum license fee of one hundred dollars on dealers of pistols, pistol cartridges, bowie knives, dirk knives.Gun shops, or gun repair shops capped at ten dollars.
Keywords: LICENSE - DEALERS